John Krige (ed.), How knowledge moves. Writing the transnational history of science and technology, Chicago, The University of Chicago Press, 2019, 444 páginas - Zunino, Dhan (Universidad Nacional de Quilmes, 2020)
Fil: Zunino, Dhan. Universidad Nacional de Quilmes; Argentina.